Discrete event simulation for production planning in modular garment manufacturing systems [Simulación de eventos discretos en la planificación de producción para sistemas de confección modular] (2018)
This article aims to solve a NP-Hard production planning problem with stochastic variables in a modular manufacturing plant of a large company.In order to minimize costs per batch amixed programming model is proposed, which is based on results of a discrete simulation model executed in MSExcel and VBApplications. The simulation model presents variables such as manufacturing modules, setup staff, space and machinery resources, among others.After find the optimal solution of the production problem, it is concluded that the discrete simulation for modular manufacturing systems is adaptable to basic software, allows to propose new scenarios, articulate complex information, customize models and facilitates parameterize alarge number of variables. © 2018 Revista Tecnica de la Facultad de Ingeniera. All rights reserved.